The Effectiveness of Implementation of Academic Regulations for FKIP University Students Labuhanbatu FY2021/2022 - Siti Kholizah Siregar; Junita Junita (Budapest International Research and Critics University, 2022)
This study aims to determine the effectiveness of the implementation of academic regulations for FKIP students at Labuhanbatu University. The type of research used is a qualitative method, which is a form of research that aims to provide an overview in the form of data collected from the field objectively with the type of descriptive research. The data collection technique used is from the results of observations and questionnaires/questionnaires. Based on the results of the study, the effectiveness of the implementation of academic regulations for FKIP students at Labuhanbatu University has been partially achieved, but there are several things that must be considered because they have not been optimally handled. This can be seen from several indicators of program effectiveness which include: (1) The accuracy of the program targets which are aimed at students have been right on target (2) Program socialization to students, and the public regarding educational programs that have been running quite effectively (3) Achievement of goals the program has not been achieved as it should be because there are still several reports of violations received by the campus (4) Monitoring of the program in which there are several things that must be addressed because it has not been effective enough in monitoring it while the program is running.